2019
DOI: 10.30848/pjb2020-1(9)
|View full text |Cite
|
Sign up to set email alerts
|

Variations in water relations, stomatal characteristics, and plant growth between quinoa and pea under salt-stress conditions

Abstract: Livestock production, and small scale and extensive grazing livestock production systems in Pakistan lack longterm sustainability due to declining quantity and quality of green forages and pastures. Information on the nutritional value of range/pasture and cultivated grass species is required to design proper strategies not only for nutritional management of grazing animals, but also for development of good quality forage resources. Therefore, the current study was planned to: (i) analyze the chemical profile … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
10
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 11 publications
(11 citation statements)
references
References 48 publications
1
10
0
Order By: Relevance
“…ese damage effects induced by salt stress suppress the wheat shoot and root growth and therefore negatively affect FW and DW. Moreover, there was a progressive reduction in the wheat's FW and DW weights with increasing NaCl level, which was compatible with previous studies [1,22]. e minimum decrease in the FW and DW in Sakha69 cultivar International Journal of Agronomy might be due to the extraeffective detoxification mechanism, including the antioxidant defence mechanisms.…”
Section: Discussionsupporting
confidence: 91%
See 1 more Smart Citation
“…ese damage effects induced by salt stress suppress the wheat shoot and root growth and therefore negatively affect FW and DW. Moreover, there was a progressive reduction in the wheat's FW and DW weights with increasing NaCl level, which was compatible with previous studies [1,22]. e minimum decrease in the FW and DW in Sakha69 cultivar International Journal of Agronomy might be due to the extraeffective detoxification mechanism, including the antioxidant defence mechanisms.…”
Section: Discussionsupporting
confidence: 91%
“…e notable decreases were observed with Sakha8, which was the most influenced cultivar by saline conditions, followed by Giza168 and Sakha69 which was the most resistant cultivar to the NaCl salt application. e response of plant growth to salinity stress varies among species and has been reported in many investigations [1,2,5,21,22]. In this consideration, Bacu et al [7] demonstrated that an increase in salt concentration (50, 100, and 200 mM NaCl) induced a significant decrease in the growth criteria (shoot, root, and leaf length) of five wheat cultivars.…”
Section: Discussionmentioning
confidence: 93%
“…These differentially expressed TFs indicated that TFs played an important part in response of B. distachyon to salt stress, which could be helpful in understanding the mechanism of salt tolerance. Stomatal opening and wax biosynthesis of epidermal cells in plant leaves alleviate ion-toxicity-induced damage by reducing water loss under salt stress [74][75][76]. One of the physiological responses regulated by ABA is related to stomatal closure, which can prevent excessive transpiration and reduce water loss [25].…”
Section: Discussionmentioning
confidence: 99%
“…During the germination under salt stress, the seeds require a higher amount of water uptake due to the accumulation of the soluble solutes around the seeds which cause an increase in osmotic pressure [22]. This results in extreme uptake of the ions which cause ion toxicity in the plant reduced the water potential gradient between external environments and the seed inhibits the primary root emergence [23].…”
Section: Germination Percentagementioning
confidence: 99%